Strength and behavior in shear of reinforced concrete deep beams under dynamic loading conditions - Adhikary, Satadru Das (2013)
Research on reinforced concrete (RC) deep beams has seen considerable headway over the past three decades; however, information on the dynamic shear strength and behavior of RC deep beams under varying rates of loads remains limited. This paper describes the experimental results of 24 RC deep beams with and without shear reinforcements under varying rates of concentrated loading. Results obtained serve as